Jeszcze teatr, czy już kino? Jeszcze kino, czy już teatr? O przestrzeniach wideo w spektaklach Heinera Goebbelsa, Roberta Lepage’a, Jose Montalvo* - Olkusz, Piotr (Przestrzenie Teorii, 2007)
The use of film techniques in theatre performances is no new invention. There are two distinguishable ways of doing this: in the first, media techniques are used on the stage only and bear no profound significance to the "actual core of the theatre" (Bśatrice Picon-Vallin, Les Les ścrans sur la scćne, Lausanne, 1998, p. 10), or rather, they are used to transform the "classic" theatrical approach (actor who "here and now" - immediately - expresses himself). With the second method, the use of multimedia cannot be considered as an optional part of performing arts: the introduction of multimedia creates profound theatrical relationships, although the "here and now" setting does not apply. (e.g. in the plays of Robert Lepage, Heiner Goebbels and Jose Montalvo). In view of the development and omnipresence of digital and interactive techniques, it seems that stage theatre intended to be "natural" can no longer ignore multimedia "as the actual core" of the theatrical relationship (it is not sufficient to simply show them on the stage). And similarly, the theory of stage theatre must modify its definitions in order to discuss this type of theatre which seeks to represent the relationships of today.